Smart Materials and Their Application in Robotic Hand Systems: A State of the Art - Paola Andrea Castiblanco; José Luis Ramirez; Astrid Rubiano (Universitas Pendidikan Indonesia, 2021)
The use of soft robotics and smart materials for the design of devices that help the population in different tasks has gained a rising interest. Medicine is one of the fields where its implementation has shown significant advances. However, there are works related to applications, directed to the human body especially in replacement of devices for the upper limb. This document aims to explore the state of the art relating to the study of soft robotics, the implementation of smart materials, and the artificial muscles in the design or construction of hand prostheses or robotic devices analogous to the human hand.